Hydrodynamic sample injection into short electrophoretic capillary in systems with a flow-gating interface - Opekar, František; Tůma, Petr (Journal of chromatography. A, 2017)
An electrophoretic apparatus with a flow-gating interface has been developed, enabling hydrodynamic sequence injection of the sample into the separation capillary from the liquid flow by underpressure generated in the outlet electrophoretic vessel. The properties of the apparatus were tested on an artificial sample of an equimolar mixture of 100μM potassium and sodium ions and arginine. The repeatability of the injection of the tested ions expressed as RSD (in%) for the peak area, peak height and migration time was in the range 0.76-2.08, 0.18-0.68 and 0.28-0.48, respectively. Under optimum conditions, the apparatus was used for sequence monitoring of the reaction between the antidiabetic drug phenyl biguanide and the glycation agent methyl glyoxal. The reaction solution was continuously sampled by a microdialysis probe from a thermostated external vessel using a syringe pump at a flow rate of 3μLmin-1 and was injected into a separation capillary at certain time intervals. The electrophoretic separation progressed in a capillary with an internal diameter of 50μm with a length of 11.5cm and was monitored using a contactless conductivity detector.
Keywords: Potassium; časové faktory; hydrodynamika; Hypoglycemic Agents; roztoky; elektroforéza kapilární; Biguanides; biguanidy; Solutions; pyruvaldehyd; Pyruvaldehyde; Arginine; Time Factors; arginin; Microdialysis; Sequence analysis; Flow-gating interface; Hydrodynamic injection; mikrodialýza; hypoglykemika; Sodium; draslík; sodík; Electrophoresis, Capillary; Hydrodynamics; Antidiabetic drug; Short capillary separation